Is endovascular treatment with multilayer flow modulator stent insertion a safe alternative to open surgery for high-risk patients with thoracoabdominal aortic aneurysm? - Pinto,C; Garas,G; Harling,L; Darzi,A; Casula,R; Athanasiou,T (Annals of Medicine and Surgery, 2017)
A best evidence topic in cardiothoracic and vascular surgery was written according to a structured protocol. The question addressed was whether endovascular treatment with multilayer flow modulator stents (MFMS) can be considered a safe alternative to open surgery for high-risk patients with thoracoabdominal aortic aneurysm (TAAA). Altogether 27 papers were identified using the reported search, of which 11 represented the best evidence to answer the clinical question. The authors, journal, date and country of publication, patient group studied, study type, relevant outcomes, results, and study limitations are tabulated. The outcomes of interest were all-cause survival, aneurysm-related survival, branch vessel patency and major adverse events. Aneurysm-related survival exceeded 78% in almost all studies, with the exception of one where the MFMS was inserted outside the instructions for use. In that study the aneurysm-related survival was 28.9%. The branch vessel patency was higher than 95% in 10 studies and not reported in one. At 12-month follow-up, several studies showed a low incidence of major adverse events, including stroke, paraplegia and aneurysm rupture. We conclude that MFMS represent a suitable and safe treatment for high-risk patients with TAAA maintaining branch vessel patency when used within their instructions for use. However, a number of limitations must be considered when interpreting this evidence, particularly the complete lack of randomised controlled trials (RCTs), short follow-up in all studies, and heterogeneity of the pathologies among the different populations studied. Further innovative developments are needed to improve MFMS safety, expand their instructions for use, and enhance their efficacy.